Mining the human gut microbiome for novel stress resistance genes - Eamonn P. Culligan; Julian R. Marchesi; Colin Hill; Roy D. Sleator (Gut Microbes, 2012)
With the rapid advances in sequencing technologies in recent years, the human genome is now considered incomplete without the complementing microbiome, which outnumbers human genes by a factor of one hundred. The human microbiome, and more specifically the gut microbiome, has received considerable attention and research efforts over the past decade. Many studies have identified and quantified “who is there?,” while others have determined some of their functional capacity, or “what are they doing?” In a recent study, we identified novel salt-tolerance loci from the human gut microbiome using combined functional metagenomic and bioinformatics based approaches. Herein, we discuss the identified loci, their role in salt-tolerance and their importance in the context of the gut environment. We also consider the utility and power of functional metagenomics for mining such environments for novel genes and proteins, as well as the implications and possible applications for future research.